2021
DOI: 10.1080/09669760.2021.1893157
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated Smartphones in Early Childhood Education and Care settings. Blurring the lines between pedagogical and administrative use

Abstract: In Norway's 'Framework Plan for kindergartens' digital tools are to be implemented for learning, play and creativity. Implicitly the concept of digital tools, or ICTs, tend to be tablets, computers, and interactive whiteboards, smartphones are as such not taken into account. However, we find that the smartphone is particularly interesting because it differs from the other types of ICTs used in Early childhood education and care (ECEC) institutions. Tablets, computers and interactive whiteboards, are all implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Both formal and informal caregivers play important roles in the context of technology for aging in place. Both formal and informal caregivers frequently speak and act on behalf of older people, especially older people with cognitive impairments when technology developers seek to identify user needs or evaluate the usefulness of the technology [ 185 - 188 ]. In doing so, they act as gatekeepers who shape what types of technology are developed and offered to older people, and equally important, which are not [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both formal and informal caregivers play important roles in the context of technology for aging in place. Both formal and informal caregivers frequently speak and act on behalf of older people, especially older people with cognitive impairments when technology developers seek to identify user needs or evaluate the usefulness of the technology [ 185 - 188 ]. In doing so, they act as gatekeepers who shape what types of technology are developed and offered to older people, and equally important, which are not [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the purpose of the technology is aimed at the needs of the older person or efficiency-related goals in care organizations rather than the improvement of the care workers’ working environment or care burden. Additionally, like all users, both formal and informal caregivers are not just impacted by technologies that enter their lives but they also shape the technology in turn [ 188 , 192 - 199 ], meaning that the implications that the technology will have in practice are never given beforehand and must always be studied in the context of use [ 185 , 187 , 200 , 201 ]. Finally, both informal and formal caregivers must frequently improvise and adapt the technology to render it functional [ 192 , 202 - 205 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during the PSBB period, the findings showed that there were challenges related to the digital divide, such as bad network connections and limited access to technology, which impeded the domestication process [26]. This finding highlights the importance of considering the social and cultural context in which technology is used and the role of socio-economic factors in shaping the domestication process.…”
Section: Figure 2 Frequent Words During Psbbmentioning
confidence: 93%
“…Smart portable devices now play a central role in people's everyday lives, both as stand-alone devices and as companions to other digital devices [5]. As companions literally from early childhood [6,7] to old age [8], smartphones and tablets with the power of supercomputers from the past are not only used as a means of communication in combination with a camera and a range of applications, but also provide access to a wealth of information and resources, making them, at least potentially, a valuable educational tool that combines formal and informal experiences [9]. While the ubiquity of these devices in pockets is becoming a fact of everyday life, their place and role in formal education is controversial, to say the least [10].…”
Section: Introductionmentioning
confidence: 99%